ANALISIS KORELASI KARAKTERISTIK TANAH (P TERSEDIA, BAKTERI PELARUT FOSFAT, C ORGANIK, DAN KAPASITAS TUKAR KATION) TERHADAP PRODUKTIVITAS JAGUNG DI KECAMATAN CIBUGEL, KABUPATEN SUMEDANG - Putri, Thausy Julia; Sule, Marenda; Fitriatin, Betty (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Maize is the main strategic food crop in Indonesia's food supply, but the productivity of maize in Indonesia is still low. Increasing the productivity of maize can be done by understanding information about the characteristics of the soil on maize planting areas. The research aimed to evaluate the relationship of soil biological and chemical characteristics (available P, phosphate solubilizing bacterial population, arbuscular mycorrhizal fungal population, organic C, and cation exchange capacity) on maize plant productivity. The research was carried out in Cibugel District, Sumedang Regency. The research used descriptive survey and comparative methods on 18 soil samples. The maize planting area was obtained based on analysis and overlapping of land units in the form of; slope, elevation, climate and shelled maize production area. Maize planting land is at an altitude of 500-1,000 meters above sea level and with a slope of 10-30%. The results of correlation analysis showed that organic C, cation exchange capacity, and phosphate solubilizing bacteria had a positive correlation with maize productivity, while available P and arbuscular mycorrhizal fungi had a negative correlation. organic C had the highest close relationship with a value of r = 0.43, while the other parameters have a weak relationship.